Who’s afraid to be a millionaire ? : - Boston, Kelvin E. (John Wiley, 2006)
You don’t need to be a financial professional to achieve your financial dreams. All you need is a plan and the discipline to follow it. Filled with Kelvin Boston’s trademark use of jargon-free language, humor, and positive thinking, Who’s Afraid to Be a Millionaire? will show you how to take control of your personal finances and make smart decisions that will positively affect your future.